2015
DOI: 10.1073/pnas.1518007112
|View full text |Cite
|
Sign up to set email alerts
|

A basal stem cell signature identifies aggressive prostate cancer phenotypes

Abstract: Evidence from numerous cancers suggests that increased aggressiveness is accompanied by up-regulation of signaling pathways and acquisition of properties common to stem cells. It is unclear if different subtypes of late-stage cancer vary in stemness properties and whether or not these subtypes are transcriptionally similar to normal tissue stem cells. We report a gene signature specific for human prostate basal cells that is differentially enriched in various phenotypes of late-stage metastatic prostate cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
172
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(191 citation statements)
references
References 76 publications
11
172
2
1
Order By: Relevance
“…This finding is consistent with previous observations of slower disease progression and decreased cellular proliferation and tumor invasion in luminal-derived prostate tumors compared with basal-derived tumors in the context of PTEN loss (18). It also coincides with our recent report that aggressive human prostate cancers are enriched for a basal stem cell expression signature (26). In contrast, however, another study found that tumors of luminal origin were more aggressive than tumors of basal origin based on cross-species bioinformatics analyses (3).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous observations of slower disease progression and decreased cellular proliferation and tumor invasion in luminal-derived prostate tumors compared with basal-derived tumors in the context of PTEN loss (18). It also coincides with our recent report that aggressive human prostate cancers are enriched for a basal stem cell expression signature (26). In contrast, however, another study found that tumors of luminal origin were more aggressive than tumors of basal origin based on cross-species bioinformatics analyses (3).…”
Section: Discussionsupporting
confidence: 93%
“…Hi basal cell 1,000 21 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Intriguingly, human basal-and luminal-derived tumors demonstrate histologically distinct phenotypes when challenged with the same oncogenes, MYC and AKT1. Tumors derived from basal cells are of a higher grade than tumors derived from luminal cells.…”
Section: Discussionmentioning
confidence: 99%
“…When we looked at the RNA-seq data, we observed that the Pparg INT tumors had an increased basal phenotype compared with the Pparg WT and Pten Null tumors (Fig. S3B), in keeping with a more aggressive phenotype (15). To rule out the effect of the transposon on genes adjacent to Pparg, we could not demonstrate any differentially expressed genes within a 200-kb flanking region around the Pparg locus in those tumors with insertions at this locus (Pparg INT ) [false discover rate (FDR)-corrected Wald test, P < 0.001; P value represents the likelihood (less than 1 in 1,000 chance) of another differentially expressed gene being found flanking a 200-kb region on either side of Pparg].…”
Section: Significancementioning
confidence: 89%
“…The corresponding power from the calculated sample size was obtained via a simulation using a two-sided Wald's test statistic in (32).…”
Section: Sample Size and Power Estimation In The Case Of Testing Multmentioning
confidence: 99%
“…Differentially expressed genes (DEGs) or novel transcripts identified by RNA-seq have served as gene signatures for clinical diagnosis, prognosis, and to estimate the efficacy of gene therapy or survival prediction [31][32][33][34][35]. With the rapid growth of clinical trial applications using RNA-seq, sample size estimation methods are critically needed for experimental design.…”
Section: Introductionmentioning
confidence: 99%